2017
DOI: 10.1152/jn.00638.2016
|View full text |Cite
|
Sign up to set email alerts
|

Coupling multielectrode array recordings with silver labeling of recording sites to study cervical spinal network connectivity

Abstract: Midcervical spinal interneurons form a complex and diffuse network and may be involved in modulating phrenic motor output. The intent of the current work was to enable a better understanding of midcervical "network-level" connectivity by pairing the neurophysiological multielectrode array (MEA) data with histological verification of the recording locations. We first developed a method to deliver 100-nA currents to electroplate silver onto and subsequently deposit silver from electrode tips after obtaining midc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…Inspiratory depolarizing signals observed by voltage imaging in both central and medial motor areas in the present study could be attributed to inspiratory activity of not only motoneurons, but interneurons. Our finding is compatible with the notion by Streeter et al ( 2017 ), and it is considered that the motoneurons and interneurons together form inspiratory neural output patterns in the phrenic and scalene microcircuits.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Inspiratory depolarizing signals observed by voltage imaging in both central and medial motor areas in the present study could be attributed to inspiratory activity of not only motoneurons, but interneurons. Our finding is compatible with the notion by Streeter et al ( 2017 ), and it is considered that the motoneurons and interneurons together form inspiratory neural output patterns in the phrenic and scalene microcircuits.…”
Section: Discussionsupporting
confidence: 94%
“…However, due to technical limitations, the presence of interneurons within the phrenic nucleus has not been thoroughly studied either physiologically or anatomically (Lane 2011 ). Recently, Streeter et al ( 2017 ) combined the techniques of multielectrode array recording and histochemistry, and mapped interneuron populations in the mid cervical spinal cord in adult rats. They suggested that a number of interneurons generate synchronous respiratory discharge with mono- and polysynaptic connections among neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to excitatory inputs from the rVRG, a complex network of interneurons throughout the spinal cord send excitatory inputs to PhMNs and can modulate DIAm activity (see reviews (Jensen et al 2019;Sunshine et al 2020)). There exist anatomical projections from interneurons in upper cervical segments to PhMNs (Dobbins & Feldman, 1994;Lane et al 2008a,b), constituting a premotor interneuron population that does not mediate inspiratory drive but may affect PhMN excitability (Lu et al 2004;Gonzalez-Rothi et al 2017;Streeter et al 2017). Following spinal cord injury, an increase in the excitatory input from these spinal interneurons may be important in recovery (Jensen et al 2019).…”
Section: Source Of Glutamatergic Innervation Of Phrenic Motor Neuronsmentioning
confidence: 99%
“…The respiratory phase dependence of these long-latency activations may reflect more than just inspiratory-expiratory oscillations in phrenic motoneuron excitability (Berger, 1979). Respiratory-related bursting patterns are often reported in cervical interneurons (Duffin and Iscoe, 1996; Hayashi et al, 2003; Hilaire et al, 1986; Lane et al, 2009; Palisses and Viala, 1987; Sandhu et al, 2015; Streeter et al, 2017b) and at least a portion of these cells can have direct input from the ventral respiratory group in the medulla (Duffin and Iscoe, 1996). Thus, oscillations in the excitability of the cervical propriospinal network, and specifically increased excitability during the inspiratory phase, may enable polysynaptic activations during inspiratory ISMS.…”
Section: Discussionmentioning
confidence: 99%
“…These longer latencies are consistent with activation of polysynaptic excitatory pathways (Borst et al, 1995; Borst and Sakmann, 1996; Meinrenken et al, 2003). Polysynaptic spinal activation of phrenic motoneurons is plausible since both neurophysiological (Marchenko et al, 2015; Sandhu et al, 2015; Streeter et al, 2017b) and anatomical data (Dobbins and Feldman, 1994; Lane et al, 2008; Lois et al, 2009) have shown mid cervical interneurons which are synaptically coupled with the phrenic motor pool. There is currently relatively little evidence, however, that cervical interneurons convey brainstem “respiratory drive” to phrenic motoneurons during spontaneous breathing (Duffin and Iscoe, 1996).…”
Section: Discussionmentioning
confidence: 99%